Expression and significance of PIBF combined with Galectin-1 in cervical precancerous lesions - Wang, Hong (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to discuss the significance of PIBF and Galectin-1 in cervical dysplasia tissue.MethodsThe expression of PIBF and Galectin-1 in precancerous tissues of cervical cancer was determined by the immunohistochemical method and ELISA method, and their clinical significance was analyzed.ResultsPIBF and Galectin-1 levels in cervicitis and CIN1 tissues showed no statistically significant difference; the levels of PIBF and Galectin-1 in CIN2 and CIN3 tissues were higher than those in cervicitis and CIN1, and the differences were statistically significant when compared with other groups in the CIN3 group.ConclusionCompared with the normal cervical lesion tissue, the levels of PIBF and Galectin-1 in the precervical lesion tissue were significantly increased, suggesting that their elevated levels are significantly associated with the progression of cervical intraepithelial neoplasia.